The impact of economic and social dimensions from CSR and firm size towards tax avoidance - Maria Ferentina Owena; Andrianantenaina Hajanirina; Mila Austria Reyes (President University Press, 2023)
This research aimed to analyze the effect of economic and social dimensions of Corporate Social Responsibility (CSR) and company size toward tax avoidance. The proxy to measure tax avoidance used in this research is Effective Tax Rate (ETR). The sample of this research uses manufacturing companies in sector consumer goods industry and basic industries and chemical listed in Indonesia Stock Exchange (IDX) for pre-covid 19 (2014 – 2018). The analysis technique used in this research is multiple linear regression analysis. The result of analysis showed that social dimension of CSR has significant negative effect on tax avoidance. This means if CSR social dimension increase then tax avoidance will decrease. Company size has significant positive effect on tax avoidance. This means if the company size is increase then tax avoidance will increase. CSR economic dimension has no significant effect towards tax avoidance.